parents analysis of the children with autism in the development in yayasan harapan mulia jambi - sutinah sutinah SUTINAH (AKPER Dharma Wacana, 2016)
Autism is a disorder growth identified byan abnormal growth appeared before 3 years old, in which children have three abnormal functions in the term of social interaction, communication and behavior. Mostly, brain disorder on children is not curable but it is treatable through early, integrated, and intensive therapy. This research was conducted at Yayasan Harapan Mulya Jambi. The purpose of this study was to analyze the role of parents toward hyperactive children growth from 6 to 30 june 2016. Qualitative study was presented descriptively. Then, Data were collected through in-depth interview, observation, and document studies. There were 6 participants having autism children (2-9 years old) and 1 therapist from Yayasan Harapan Mulia Jambi.There were 5 themes emerged in this study, they were 1)the perspective of parents toward hyperactive children, 2) the role of parents toward hyperactive children, 3) the perspective of parents toward behavior changes occurred on hyperactive children , 4) the parents’ expectation toward children growth changes, and 5) obstacle in doing the role.The study revealed that some of parents had done the role optimally based on their children need. Although they had not known well their children need. Also, there were some obstacles to do their role. Good role of parents can assist in increasing hyperactive children growth.